Desenvolvimento de partículas lipídicas contendo alumínio-cloro ftalocianina para aplicação na terapia fotodinâmica do câncer de pele - Almeida, Ellen Denise Prado (2014)
Skin cancer is the malign tumor most common worldwide and nonmelanoma is the kind of cancer most treatable. However, nowadays there is not a ideal treatment of the skin cancer and the surgery is the therapeutic standard for treatment of malign lesion in the skin. Photodynamic therapy (PDT) consists of the administration and accumulation of photosensitizers in target cells, followed by exposure to a light source with appropriate wavelength, resulting in the formation of oxygen reactive species, responsibles for causing damage to cancerous cells. Lipid nanoparticles (LN) offer an attractive system for delivery of lipophilic drugs such as Chloroaluminium Phthalocyanine (ClAlPc) for use in PDT of skin cancer. The objective of this work was develop and characterize LN containing ClAlPc for subsequent application to the treatment of skin cancer by PDT. Solid Lipid Nanoparticles (SLN) and Nanostructured Lipid Carriers (NLC) were prepared with 20 and 40% of Oleic Acid (OA) by the method of diffusion in aqueous solvent, using Stearic Acid (SA) as solid lipid and OA as liquid lipid. The characterization was performed by Transmission Electronic Microscopy (TEM), particle size, zeta potential, entrapment efficiency (EE), drug loading and thermal analysis by Differential Scanning Calorimetry (DSC). The in vitro penetration studies were performed in modified Franz diffusion cells using pig ear skin as membrane model. The distribuition of ClAlPc in the skin layers was visualized by fluorescence microscopy using mice hairless in the in vivo studies. The LN presented nanometric size with high values of zeta potential and relatively spherical shape and the incorporation of OA promoted the increase of EE and drug loading reaching values of 95.8% and 4%, respectively. The thermal analysis showed the presence of polymorphism, due to the process of melting and recrystallization of the lipid. In vitro penetration studies, ClAlPl was not detected in receptor medium, being retained in stratum corneum and skin layers and showed the penetration ability of the formulations developed, since the amount of ClAlPc retained on the skin was significantly higher (p < 0,01) compared the control formulation. The formulation with 40% AO (NLC 40) showed amount of drug retained in the skin significantly higher (p<0,01) compared to other formulations, demonstrating the enhancer effect of penetration of the OA, besides favoring the transport of ClAlPc to deeper layers of the skin, due to the smaller particle size of this formulation. According to the results obtained, the systems developed may be promising for the incorporation of AlClPc in the treatment of skin cancer by PDT.